Atención selectiva y memoria de trabajo en niños y niñas con Síndrome de Down : revisión de avances teóricos (2021)
Down Syndrome (DS) is a genetic disorder that causes a decrease in cognitive processes, such as Selective Attention (SA) and Working Memory (TM). These issues have been little addressed in scientific research; For this reason, this article aims to analyze the theoretical advances of the AS and TM categories in boys and girls with Down Syndrome (DS), from the subcategories: theoretical progress, evaluation, diagnosis and intervention, with the purpose of serving as a basis for future research and helping to generate strategies on these little-addressed issues